Comparative analysis of the technical characteristics of refrigerants and its effects on the environment (Publicaciones en Ciencias y Tecnología, 2021)
Currently there are different types of refrigerants used in cooling systems. To choose the ideal fluid, it is necessary to consider the thermodynamic properties such as condenser and evaporator pressure, boiling, critical and freezing temperatures, specific volume, enthalpy, which allow a maximum cooling capacity with a minimum power demand; additionally, observe that the environmental effects are low and do not cause damage to the ozone layer as a consequence of the destructive action of the chlorine-containing compounds from the decomposition of the CFC and HCFC molecules. This is a comparative-descriptive research that aims to analyze the technical characteristics of refrigerants and their effects on the environment. The data were collected from a research review, defining the current situation and future trends of the same; Presenting them in a comparative summary table highlighting the changes made from the implementation of international agreements from the Montreal Protocol to the Paris Protocol, which promote the reduction of the emission of these gases into the atmosphere.
Keywords: ozone layer; technical characteristics; environment; refrigerant